Social assistance strategies as means of addressing poverty: lessons for South Africa - Mampuru, Tsebo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2016)
Poverty is a daily reality which a majority of South Africans live with. Social security in the form of cash grants has been the main poverty reduction instrument, albeit with limited success. The thesis aims to propose improvements which can be made in the government's current social protection system and formulate alternative directions towards reducing poverty. An overview of the three most researched social security strategies around the world (i.e. Nordic, Latin American, and U.S. models) revealed two dominant instruments: conditionality and universalism. If applied in South Africa, universalism may be costly and unsustainable unless the right funding method is used. Attaching education and health attainment conditions to an adult grant would be inefficient and even burdensome to recipients. In terms of child grants, there is little evidence to suggest that the demand for and private levels of investment in education and health are insufficient. Therefore attaching health and education conditions to social grants may only serve to highlight the severe supply side inefficiencies in South Africa. Attaching marriage as an alternative condition may disadvantage poor and needy beneficiaries as marriage is an expensive institution in South Africa. Furthermore, enforcing the marriage condition would violate the constitutional rights of recipients who do not necessarily place a high value on the institution. To strengthen the poverty reduction efficiency of social grants and reduce dependency, the thesis suggests that social cash grants, regardless of whether universal and/or conditional or neither, should be temporary and used in conjunction with other strategies which encourage inclusive economic growth. Social assistance alone will not reduce poverty and ultimately, inclusive economic growth remains a more viable approach to reducing poverty. How to achieve the required inclusive economic growth in South Africa therefore provides further research opportunities.
Keywords: Uncatalogued